TAFSIR AL-QUR'AN SURAT AL-LAHAB TENTANG QASHASH SEBAGAI MATERI DAN METODE PENDIDIKAN AKHLAK - Nur Ali Subhan (Lembaga Kajian dan Pemberdayaan Mahasiswa UIN Prof. KH. Saifuddin Zuhri Purwokerto, 2019)
The surah Al-Lahb is in 111 number of surah in Quran, that is Makky means, that surah Al-Lahb is received by Rasulullah when Rasulullah still in Makkah. The surah is tell about the uncle of Rasulullah names Abu Lahab that is being from high level family and tribes that make him arrogant and cannot accept da’wa of Rasulullah. Abu Lahab is always make effort to do bad things in da’wa Rasulullah and he want Rasulullah’s da’wa is failed, his wife also help him to do this bad things. Because of that, Allah swt is cursed him and his wife and entered them to the hell. Abu Lahab is become one of name surah in Quran, that is become prove of history about the bad manner of Abu Lahab to Rasulullah. The method of Qisah ( At-Tarbiyah bil al-Qishah ) in surah Al-Lahb is one of interesting method in education. This is way of Quran to explain about phropet and also others to give attention and take learning. This method is bring big impact to increase interesting and also increase inteligention of thingking because that every story is have beauty and hikmah so, that will easy to remember and to understand. There are three values of Akhlaq Education in surah Al-Lahb. There are liar, arrogant, and spiteful. That akhlaq is must be avoid because that will bring harm to ourselves, families, and society.